(untitled) (Research, Society and Development, 2022)
Introduction: Nursing, the largest category in the health area, composed of auxiliaries, technicians and nurses. Historically, this class carries out its work activities facing precarious working conditions. The Covid-19 pandemic exacerbated issues of the nursing work process, even threatening the survival of these professionals. Objective: to describe the profile of nursing professionals working in cohort units in a University Hospital during the Covid-19 pandemic. Objective: to describe the profile of nursing professionals working in cohort units in a University Hospital during the Covid-19 pandemic. Method: quantitative, observational, descriptive study. An electronic questionnaire was used on the Google forms platform, answered by nursing professionals working in cohort units of Covid-19 in a University Hospital of the State of Rio de janeiro. Data stored in Excel 2010 and analyzed by simple statistics. The project was approved by the Research Ethics Committee. Results: 220 professionals participated, 71.1% nursing technicians participated, 78.8% declared themselves female, with a predominant age range between 40 and 44 years (21.9%). They had a temporary bond of 83.9%, working for at least three months in the units, evidencing the precariousnature of work, since the temporary bond deprives the professional of labor rights. (75%) claimed to have a second bond; 60.3% worked 60 hours a week. 72.6% had a second bond and worked in the cohort sector, thus increasing the exposure to the virus and the risk of contamination of these professionals. 28.1% of the participants reported having some comorbidity such as hypertension, obesity, asthma and diabetes. Conclusion: the female gender, the double bond and the excessive workload were factors that increased the exposure of nursing professionals to SARS-CoV-2, compromising the physical, mental and social health of these individuals.